2022
DOI: 10.1186/s41182-022-00415-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental COVID-19 vaccine hesitancy for children with neurodevelopmental disorders: a cross-sectional survey

Abstract: Background Little is known about parental coronavirus disease 2019 (COVID-19) vaccine hesitancy in children with neurodevelopmental disorders (NDD). This survey estimated the prevalence and predictive factors of vaccine hesitancy among parents of children with NDD. Methods A nationally representative cross-sectional survey was conducted from October 10 to 31, 2021. A structured vaccine hesitancy questionnaire was used to collect data from parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
3
25
1
Order By: Relevance
“…This study also revealed higher Vaccine Hesitancy among parents who think that COVID-19 vaccine is not effective in controlling the disease. Similar results were also seen in a study conductedAli et al (aOR=3.22; p<0.001) 18. Perceived Susceptibility (p=0.005), perceived barriers (p<0.001) and perceived benefit were seen to be significantly associated with Vaccine hesitancy.…”
supporting
confidence: 87%
“…This study also revealed higher Vaccine Hesitancy among parents who think that COVID-19 vaccine is not effective in controlling the disease. Similar results were also seen in a study conductedAli et al (aOR=3.22; p<0.001) 18. Perceived Susceptibility (p=0.005), perceived barriers (p<0.001) and perceived benefit were seen to be significantly associated with Vaccine hesitancy.…”
supporting
confidence: 87%
“…The final pool of the studies comprised a sample size ranging from 223 to 5,237 participants with an average study sample of 1,325 and a total of 23,854 participants across all eighteen studies included (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Our review included a total of one study from Afghanistan, five from Bangladesh, eight from India and four from Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…The likelihood of vaccination was higher if the child was older, free from any comorbid conditions, and in those who were up-to-date in their routine vaccination schedule. The main concerns of hesitant parents were the novelty of the COVID-19 vaccine ( 18 ), not being convinced by the vaccine's effectiveness ( 19 ), or being unconcerned about COVID severity in childhood ( 20 ).…”
Section: Introductionmentioning
confidence: 99%